Sustainable development goals at university: the technical architect and graduate in building as an agent of urban and architectural design - Antonio Espínola Jiménez; Francisco Javier Lafuente Bolívar; Jonathan Moreno Collado; David Hidalgo García (Revista de Expresión Gráfica en la Edificación, 2025)
The University, as a transmitter and driver of knowledge, plays a crucial role in achieving the Sustainable Development Goals (SDGs). SDG 4 focuses on ensuring ‘Quality Education’ and is the starting point for achieving the other SDGs. This study takes a journey through each SDG, highlighting the responsibility that Technical Architects or Graduates in Building have in all areas, especially in the area of Graphic Expression, as they are responsible for the design and implementation of urban and built environments and have a duty to ensure that they are sustainable, safe, accessible and inclusive. Furthermore, the presence of the SDGs in 21 degrees taught in Spanish universities is verified, showing limited research and scientific production and a reduced integration of the SDGs in teaching guides. It is concluded that there is a deficit in the development of competences related to the SDGs.